Hydrothermal vent chimney-base sediments as unique habitat for meiobenthos and nanobenthos: Observations on millimeter-scale distributions - Bernhard, Joan M.; Nomaki, Hidetaka; Shiratori, Takashi; Elmendorf, Anastasia; Yabuki, Akinori; Kimoto, Katsunori; Tsuchiya, Masashi; Shimanaga, Motohiro (Frontiers in Marine Science, 2023)
Hydrothermal vents are critical to marine geochemical cycling and ecosystem functioning. Although hydrothermal vent-associated megafauna and chemoautotrophic prokaryotes have received extensive dedicated study, smaller hydrothermal vent-associated eukaryotes such as meiofauna and nanobiota have received much less attention. These communities comprise critical links in trophic flow and carbon cycling of other marine habitats, so study of their occurrence and role in hydrothermal vent ecosystems is warranted. Further, an understudied vent habitat is the thin sediment cover at the base of hydrothermal vent chimneys. An initial study revealed that sediments at the base of vent chimneys of the Izu-Ogawasara Arc system (western North Pacific) support metazoan meiofauna, but very little is known about the taxonomic composition and abundance of the meiobenthic protists and nanobiota, or their millimeter-scale distributions. Using the Fluorescently Labeled Embedded Coring method (FLEC), we describe results on meiofaunal and nanobiota higher-level identifications, life positions and relative abundances within sediments from three habitats (base of vent chimneys, inside caldera but away from chimneys, and outside caldera) of the Myojin-Knoll caldera and vicinity. Results suggest that the chimney-base community is unique and more abundant compared to non-chimney associated eukaryotic communities. Supporting evidence (molecular phylogeny, scanning and transmission electron microscopy imaging) documents first known hydrothermal-vent-associated occurrences for two protist taxa. Collectively, results provide valuable insights into a cryptic component of the hydrothermal vent ecosystem.